Smart cities and infrastructure (UN New YorkUS, 2016)
Presents key urbanisation trends and their links to the 2030 Agenda for Sustainable Development. Provides an explanation of the term smart city and describes the main components of smart infrastructure. Elaborates the five main challenges encountered in the implementation of smart infrastructure projects and underlines the key role of science, technology and innovation.
Report of the Secretary-General